Association of g.331T>C and g.1909T>C locus in KISS1 gene with fecundity traits of Kacang and Boerka goats - MASKUR MASKUR; RAHMA JAN; LESTARI LESTARI; TAPAUL ROZI; MUHAMMAD MUHSININ (Society for Indonesian Biodiversity, 2023)
Abstract. Maskur, Jan R, Lestari, Rozi T, Muhsinin M. 2023. Association of g.331T>C and g.1909T>C locus in KISS1 gene with fecundity traits of Kacang and Boerka goats. Biodiversitas 24: 4870-4876. The neuropeptide kisspeptin encodes the KISS1 gene and is crucial for reproductive system signals. This study aimed to identify polymorphisms of fecundity genes by observing candidate genes for prolific traits, namely the KISS1 gene (exon 1 and intron 1), and their relationship with litter size in Kacang and Boerka goats (Capra aegagrus hircus). The total sample used was 211 female goats. The stages of the research included DNA extraction, PCR amplification and genotyping. The association of KISS1 gene genotypes with litter size traits in Kacang goats and Boerka was analyzed using the SAS 9.1.3 software with General Linear Model (GLM) procedure. The results showed that the g.331T>C locus of the KISS1 exon 1 gene was monomorphic in all Kacang and Boerka goats populations. The locus g.1909T>C of the KISS1 intron 1 gene was polymorphic in all Kacang and Boerka goats populations. The locus g.1909T>C of the KISS1 intron 1 gene found three genotypes (TT, AT, AA). The frequency of allele T (0.775 and 0.815) was higher than allele A (0.225 and 0.185) in all Kacang and Boerka goats populations. The association of TT and AT genotypes with litter size significantly differed from that of the AA genotype in the Kacang goat. Meanwhile, in the Boerka goat, the TT genotype significantly differed from the AT and AA genotypes. The goat KISS1 gene polymorphism is critical to reproductive function and may be a reproductive characteristic marker.